2020
DOI: 10.1111/sms.13743
|View full text |Cite
|
Sign up to set email alerts
|

Light‐intensity physical activity derived from count or activity types is differently associated with adiposity markers

Abstract: Aim The aim of this study was to compare the association between count‐ and activity type–based definitions of light‐intensity physical activity (LIPA) and adiposity markers. Methods A total of 516 Danish workers participated in 1‐4 days of hip‐ and thigh‐based accelerometer measurements. Three definitions of average daily time spent in LIPA were derived: LIPA (1) time spent between 100 and 2029 CPM, LIPA (2) time spent moving and slow walking, and LIPA (3) time spent moving, walking slow, and standing. Adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…38 Other research showed that patterns of light movement had inconsistent associations with adiposity in adolescents. 37 The results of current study support these findings as linear spline models showed that stronger associations with fitness test performance were observed within the middle of the MIMS' distributions, with nonlinear patterns observed toward lower MIMS values that potentially represented less movement accumulated during the day. Additionally, Peak 60-min and Peak 30-min MIMS had stronger associations with tests of muscular strength and endurance.…”
Section: Perspectivesupporting
confidence: 82%
See 3 more Smart Citations
“…38 Other research showed that patterns of light movement had inconsistent associations with adiposity in adolescents. 37 The results of current study support these findings as linear spline models showed that stronger associations with fitness test performance were observed within the middle of the MIMS' distributions, with nonlinear patterns observed toward lower MIMS values that potentially represented less movement accumulated during the day. Additionally, Peak 60-min and Peak 30-min MIMS had stronger associations with tests of muscular strength and endurance.…”
Section: Perspectivesupporting
confidence: 82%
“…Given the results of this study, public health messaging should emphasize the importance of increased movement in children and adolescents to reap the greatest health benefits. Although some movement has shown potential benefit across the physical and mental health domains in adults, the associations between smaller amounts of movement in youth with health outcomes are inconsistent across studies 37 . Results from this study still support a mostly linear association between higher movement volume and more favorable performances on health‐related fitness tests, especially when accumulation of MIMS falls within the middle of its distribution (middle percentiles).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Examples of SB include sitting, sleeping, and other activities with very little body movement [ 13 ]. LPA can be exemplified by activities such as casual walking and light household chores [ 14 ], MPA can include activities such as brisk walking, cycling at a moderate pace, or light jogging. Lastly, VPA would include activities such as running and sprinting [ 15 ].…”
Section: Introductionmentioning
confidence: 99%